2020
DOI: 10.1088/1742-6596/1641/1/012073
|View full text |Cite
|
Sign up to set email alerts
|

Assessing E-Commerce Success from a Millennial Perspective in Indonesia

Abstract: This research was conducted to assess the success of e-commerce from the perspective of the millennial generation in Indonesia. This research was conducted through a case study on the Bukalapak Application, which in recent times has decreased from the perspective of the number of visitors. This study refers to the DeLon and McLean Updated Information System Success Model. The measurement indicators used in this study were modified based on a review of several recent studies. Data collection was carried out usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
1
1
0
1
Order By: Relevance
“…The study findings, which indicate no significant influence of e-commerce information quality on e-commerce use, are consistent with the findings of Angelina et al (2019). However, they differ from the results reported in the studies conducted by Ramadhanti and Slamet (2020), Chen et al (2019) and Mahendra et al (2020). These studies found that information quality indeed has a positive effect on the use of the system and net benefits.…”
Section: E-commerce Information Quality and Performance Of Smessupporting
confidence: 78%
“…The study findings, which indicate no significant influence of e-commerce information quality on e-commerce use, are consistent with the findings of Angelina et al (2019). However, they differ from the results reported in the studies conducted by Ramadhanti and Slamet (2020), Chen et al (2019) and Mahendra et al (2020). These studies found that information quality indeed has a positive effect on the use of the system and net benefits.…”
Section: E-commerce Information Quality and Performance Of Smessupporting
confidence: 78%
“…Respondents is more sensitive to services quality provided by Shopee app. This evidence supported by a study that found service quality has a stronger influence in determining user satisfaction in Bukalapak app (Mahendra et al, 2020).…”
Section: The Influence Of Service Quality On User Satisfactionsupporting
confidence: 63%
“…The popularity of online shopping among millennials is increasing very quickly and in many different ways. Moreover, the utilization of e-commerce is impacted by the millennial generation (Mahendra et al, 2020). The millennial generation is a creative generation that is connected to the online world and swiftly adapts to all technology-related activities, including how to perform online purchases.…”
Section: E-commerce Equation Parameter Estimation Resultsmentioning
confidence: 99%